Hedonic analysis of factors affecting sales price of flatted factory units: evidence from Korea - Oh, Saejoon (International Journal of Strategic Property Management, 2019)
Recently flatted factories have drawn attention as investment goods from developers and investors. The strengths and merits of these investments are that they are low priced and less strictly regulated. The purpose of this study is to empirically analyse the factors affecting the price of flatted factories by using the real transacted sales prices of 785 flatted factory units in Seoul and Gyeong-gi Province, Korea. A Hedonic Price Model (HPM) is employed for the study. The result finds that the price of flatted factories is affected by various factors: Location, Property, and Unit characteristics. In addition, the result outlines that flatted factories have commercial and industrial characteristics of both office buildings and factories. The result confirms that flatted factory price is affected by both industrial transportation accessibility and local transportation convenience. It also finds that property characteristics, such as gross area, age of the building, ratio of amenity facilities, core location, and parking space count are significant factors affecting the value. Moreover, the availability of floor level and two balcony unit types significantly relates to the price. Based on the results, it is also verified that the price of flatted factories is affected by factors similar to those of apartments or office buildings. This means that price decision factors of commercial and residential properties should be considered.